การศึกษาเปรียบเทียบประสิทธิภาพของการฟอกเลือดแบบออนไลน์ฮีโมไดอะฟิลเตรชั่นกับแบบคอนเวคทีฟ คอนโทร ดับเบิ้ลไฮ-ฟลักซ์ ฮีโมไดอะฟิลเตรชั่น - จุลภัทร ยศสุนทรากุล (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Background. Convective therapies have more effective to remove larger toxic molecules than conventional hemodialysis. Although on-line hemodiafiltration (on-line HDF) could provide both diffusion and convection, the procedure needs a sophisticated and expensive hemodiafiltration machine. Convective-control double high-flux hemodiafiltration (CC-DHF) was set up only a standard hemodialysis machine and using two high flux dialyzer. Aim of this study was to compare beta-2 microglobulin removal between two HDF techniques. Method. Experimental cross over trial between on-line HDF and CC-DHF was performed in 12 chronic hemodialysis patients who had treatment with hemodialysis for at least 6 mo. To eliminate confounding factors, on-line HDF was also set up using two high-flux dialyzers connected in serial. The replacement flow rate in both techniques were 25% of blood flow rate in post dilution. Result. There were no significant differences in basic hemodialysis data among on-line HDF and CC-DHF groups. On-line HDF could provide higher total beta-2 microglobulin clearance than CC-DHF (134.55+-16.18 vs.112.38+-17.03 ml/min, p<0.05). For dialysate clearance (convection+diffusion), on-line HDF also provide higher dialysate clearance than CC-DHF, but there were no significant differences in adsorptive clearance. There were no significant differences in value of Kt/Vurea and phosphate clearance between on-line HDF and CC-DHF (2.33+-0.45 vs. 2.4+-0.37 and 244.41+-77.37 vs. 242.83+-57.04 ml/min). Conclusion. On-line HDF could provide higher beta-2 microglobulin removal than CC-DHF, magnitude of which is correlated to constant rate of fluid replacement.